2015
DOI: 10.1159/000371861
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Cost-Analysis of Complications after Major Abdominal Surgery

Abstract: Background: Complications after major abdominal surgery (MAS) are associated with increased morbidity and mortality. Rising costs in health care are of increasing interest and a major factor affecting hospital costs are postoperative complications. In this study, the costs associated with complications are assessed. Methods: Retrospective cohort study of 399 consecutive patients that underwent MAS. Analysis of total costs for hospital stay, complications and treatment was performed, including bootstrapping; al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 18 publications
4
34
0
2
Order By: Relevance
“…For comparison, a study from the VU University Medical Centre in Amsterdam demonstrated that 20% of patients undergoing major gastrointestinal surgery had major complications and 15% of patients had minor complications. 8 The complication rates reported in this study appear to be consistent with international registry-based reports and may suggest that the quality of surgical skill and care provided by the WDGMC CRU is of international standard. 9 The majority of patients undergoing major colorectal resections are assessed by either a geriatrician or intensivist preoperatively and operations are often scheduled to allow for a period of prehabilitation -a well defined program to optimise the patient's physiological condition prior to surgery.…”
Section: Surgical Complications and Readmissionssupporting
confidence: 85%
“…For comparison, a study from the VU University Medical Centre in Amsterdam demonstrated that 20% of patients undergoing major gastrointestinal surgery had major complications and 15% of patients had minor complications. 8 The complication rates reported in this study appear to be consistent with international registry-based reports and may suggest that the quality of surgical skill and care provided by the WDGMC CRU is of international standard. 9 The majority of patients undergoing major colorectal resections are assessed by either a geriatrician or intensivist preoperatively and operations are often scheduled to allow for a period of prehabilitation -a well defined program to optimise the patient's physiological condition prior to surgery.…”
Section: Surgical Complications and Readmissionssupporting
confidence: 85%
“…To decrease the risk of unwanted postoperative outcomes, optimising the health status of a patient before (oncological) surgery is increasingly regarded as an important part of the preoperative treatment process [6,7,8,9]. Optimising functional performance by an exercise program before a major invasive surgical procedure is called prehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of these complications leads on the one hand to prolonged and increased patient suffering, and on the other hand to the increase in average cost by 50% (8). In patients with gastric cancers, besides local etiopathogenic factors common to those of benign pathology, other general factors such as anaemia, hypoproteinaemia and advanced age may also intervene.…”
Section: Eja -Oeso-jejunal Anastomosis Gja -Gastro-jejunal Anastomosmentioning
confidence: 99%